The Role of Internet Technology in E-Commerce - Sukma Nugraha; Dini Nuraeni (Journal Civics And Social Studies, 2021)
This research discusses the role of internet technology in e-commerce. This research used a causal research design on 58 respondents. The data collection technique used is simple linear regression with the SPSS 21 application. Technology plays a role in the development of e-commerce. This shows that customers will be satisfied if they use technology that offers good technology, low risk and the development of e-commerce. This research has benefits in developing applied theory that information technology plays an important role in e-commerce. For further research, it is hoped that we will examine dividend variables that are not included in this research model. This research has practical benefits for business actors using e-commerce to improve marketing performance by always paying attention to the role of information technology in e-commerce.